DIVERSITY OF NEPHENTHES SPP SPECIES IN THE EDUCATION FOREST OF MUHAMMADIYAH UNIVERSITY OF PALANGKA RAYA: KEANEKARAGAMAN SPESIES NEPENTHES SPP SPECIES IN THE EDUCATION FOREST OF MUHAMMADIYAH UNIVERSITY OF PALANGKA RAYA - Ardiyansyah Purnama; Mariaty Mariaty (Anterior Jurnal, 2023)
Biodiversity, one of which is the diversity of species of Nepenthes spp, is a natural wealth owned by the Education Forest of the Muhammadiyah University of Palangkaraya, Rakumpit, Palangka Raya City, Central Kalimantan. The research uses observation techniques and transect techniques as well as literature documentation as a supporting source with this type of exploratory research. The diversity of Nepenthes spp species obtained in the Educational Forest of Muhammadiyah University of Palangkaraya, namely found 6 (six) species with different characteristics of roots, stems and leaves. Nepenthes spp species found included Nepenthes ampullaria jack, Nepenthes rafflesiana jack, Nepenthes reinwardtiana miq, Nepenthes hirsute, Nepenthes garcilis, and Nepenthes tomoriana.